Specific Distribution of Phosphatidylglycerol to Photosystem Complexes in the Thylakoid Membrane - Kobayashi, Koichi; Endo, Kaichiro; Wada, Hajime (Frontiers in Plant Science, 2017)
The thylakoid membrane is the site of photochemical and electron transport reactions of oxygenic photosynthesis. The lipid composition of the thylakoid membrane, with two galactolipids, one sulfolipid, and one phospholipid, is highly conserved among oxygenic photosynthetic organisms. Besides providing a lipid bilayer matrix, thylakoid lipids are integrated in photosynthetic complexes particularly in photosystems I and II and play important roles in electron transport processes. Thylakoid lipids are differentially allocated to photosynthetic complexes and the lipid bilayer fraction, but distribution of each lipid in the thylakoid membrane is unclear. In this study, based on published crystallographic and biochemical data, we estimated the proportions of photosynthetic complex-associated and bilayer-associated lipids in thylakoid membranes of cyanobacteria and plants. The data suggest that ~30 mol% of phosphatidylglycerol (PG), the only major phospholipid in thylakoid membranes, is allocated to photosystem complexes, whereas glycolipids are mostly distributed to the lipid bilayer fraction and constitute the membrane lipid matrix. Because PG is essential for the structure and function of both photosystems, PG buried in these complexes might have been selectively conserved among oxygenic phototrophs. The specific and substantial allocation of PG to the deep sites of photosystems may need a unique mechanism to incorporate PG into the complexes possibly in coordination with the synthesis of photosynthetic proteins and pigments.